Brainstem and limbic encephalitis with paraneoplastic neuromyelitis optica. (January 2016) - Moussawi, Khaled; Lin, David J.; Matiello, Marcelo; Chew, Sheena; Morganstern, Daniel; Vaitkevicius, Henrikas
Highlights: Brainstem and limbic encephalitis can be a manifestation of paraneoplastic neuromyelitis optica (NMO) associated with breast cancer. Prognosis of paraneoplastic NMO is favorable when treated with immunotherapy and cancer resection. Abstract: The spectrum of disorders associated with anti-neuromyelitis optica (NMO) antibody is being extended to include infrequent instances associated with cancer. We describe a patient with brainstem and limbic encephalitis from NMO-immunoglobulin G in serum and cerebrospinal fluid in the context of newly diagnosed breast cancer. The neurological features markedly improved with excision of her breast cancer and immune suppressive therapy. This case further broadens the NMO spectrum disorders (NMOSD) by an association between NMOSD and cancer and raises the question of coincidental occurrence and the appropriate circumstances to search for a tumor in certain instances of NMO.